The role of obstetric knowledge in utilization of delivery service in Nepal - Karkee, R.; Baral, O.; Khanal, Vishnu; Lee, Andy (Oxford University Press, 2014)
Birth Preparedness and Complication Readiness (BP/CR) program has been promoted in Nepal to equip pregnant women with obstetric knowledge so as to motivate them to seek professional care. Using a prospective design of 701 pregnant women of more than 5 months gestation in a central hills district of Nepal, we evaluated if having obstetric knowledge could make a difference in maternal delivery behaviour. The results suggested that BP/CR program was effective in raising women’s obstetric knowledge, which was significantly associated with facility delivery according to logistic regression analysis. In particular, women who acknowledged that unexpected problems could occur during pregnancy and childbirth were more likely (odds ratio [OR] 5.83, 95% confidence interval [CI] 2.95–11.52) to deliver at a health facility than others unaware of the possible consequences. Similarly, women who knew any antepartum danger sign (OR 2.16, 95% CI: 1.17–3.98), any intrapartum danger sign (OR 3.80, 95% CI: 2.07–6.96) and any postpartum danger sign (OR 3.47 95% CI: 1.93–6.25), tended to deliver at a health facility. Convincing and counselling the pregnant women of the health consequences of pregnancy and childbirth would increase their utilization of delivery service.